Synthesis and electrochemical characterization of a new benzodioxocine-fused poly(N-methylpyrrole) derivative: a joint experimental and DFT study. (2nd November 2020) - Kurtay, Gülbin; Soganci, Tugba; Sarikavak, Kübra; Ak, Metin; Güllü, Mustafa
Abstract : Synthesis of a new electropolymerizable monomer, XyPMe, regarding the reaction of diethyl N -methyl-3, 4-dihydroxypyrrole-2, 5-dicarboxylate and 1, 2-bis(bromomethyl)benzene with concomitant hydrolysis and decarboxylation reactions was accomplished. Abstract : In this study, our findings from experimental studies were presented on the synthesis of a new electropolymerizable monomer, 2-methyl-5, 10-dihydro-2 H -benzo[6, 7][1, 4]dioxocino[2, 3- c ]pyrrole (XyPMe), regarding the cyclization reaction of diethyl N -methyl-3, 4-dihydroxypyrrole-2, 5-dicarboxylate and 1, 2-bis(bromomethyl)benzene with concomitant hydrolysis and decarboxylation reactions. The critical step in this synthetic pathway was to determine the optimal temperature of decarboxylation utilizing TGA analysis, which decreases in situ polymerization side-product formation significantly. Following the preparation of the target monomer, the electropolymerization reaction was then conducted, and the optoelectronic properties were investigated in detail. In order to better illuminate the effects of N -alkylation and the heterocyclic ring system on the polymer backbones, we have included and theoretically studied the electronic properties of two monomers already synthesized in our laboratory, possessing the butyl group on the pyrrole ring (XyPBu) and the thiophene scaffold on its structure (XyT), and their corresponding oligomers ( n = 2 to 11, n indicates the consecutive unit number). This combined experimental and theoretical research provides a pathway for advanced conjugated systems with predictable electronic and structural properties to be established.